Understanding prejudice, racism, and social conflict - Augoustinos, Martha; Reynolds, Katherine J. (SAGE, 2001)
Written for students and academics working in the social sciences, Understanding Prejudice, Racism and Social Conflict integrates a variety of approaches to understanding these issues whilst suggesting new ways of studying these complex problems.